Museums, cultural hybridization and new territorialities (Cadernos de Sociomuseologia, 2014)
The text seeks to present the complex relationships between the different notions of state, along the modern and postmodern period and the place and the role played by museums. Emphasize the importance of the political, social, educational and cultural context was the construction of the museum as a public space in Europe and consequently in most western countries since the French Revolution to the present day. In contemporary notions of heritage and its processes, identity, socialization, role play, communication and education are part of the museum universe whether traditional museums whether socially committed museums. Given the processes of globalization and cultural hybridization, the museums are scenes for discussions on the issues of territoriality, new categories of assets as well as new understandings of users / beneficiaries of the museum institution.Key words: Heritage; Memory, cultural hybridization; Sociomuseology; cultural policy